Conspiracy Beliefs and Covid-19 Vaccination Hesitancy in Italy: A Cross-Sectional Study - Cau, Silvia; Portelli , Valeria; Lino Maria Presti , Giovambattista (Journal of Health Education, 2024)
Background: This cross-sectional study examines sociodemographic characteristics and conspiracy beliefs among vaccinated and unvaccinated during the COVID-19 pandemic. Methods: 317 Italian-speaking participants were surveyed online, categorized by vaccination status. Sociodemographic variables were compared, and an exploratory factor analysis assessed conspiracy beliefs. Results: Of 217 vaccinated and 100 unvaccinated participants, differences in demographics and vaccine-related attitudes were observed. Vaccinated individuals sought more information online and had lower conspiracy beliefs than unvaccinated individuals. The exploratory factor analysis revealed a single factor, which was found to be significantly higher among unvaccinated participants, suggesting a correlation between vaccine hesitancy and belief in conspiracy theories. Conclusion: Addressing conspiracy beliefs may help increase vaccination rates in Italy. The study's limitations and implications for future research are discussed.